Social Facilitation: the Kaliningrad Region and Russian Mainland Regions - Toropov, P.; Samsonova, N. (Baltic Region, 2015)
The authors look at the concept of social facilitation as a possible component of Russian social consolidation in the course of social reforms. The article focuses on the results of an empirical study of the levels and characteristics of competence in social facilitation, which is here understood as the ability to apply certain knowledge and systems of skills and as a success rate of actions based on experience in improving the conditions of social development. The study was conducted in the Kaliningrad region in 2012—2013. The data was obtained through a survey of 400 respondents using the authors’ methodology encompassing eight basic elements of competence and a structured interview aimed at a better understanding of the subject of the study and attitudes towards it. The data is compared against the results of a similar study in two regions of central Russia with similar conditions. The results suggest a disharmonic and inconsistent structure of competence in social facilitation, low motivation for social activity in youth, and a narrow range of ideas about possible areas of personal activities in the current conditions. Gender differences are identified in the level and structure of competence. The authors believe that certain differences in competence components identified through mathematical methods are determined by the geographical characteristics of the Kaliningrad region — its exclave nature, a relatively small territory, and proximity to the EU countries. It is stressed that the regional conditions affecting motivation, forms and areas of activities, and structure of experience should be taken into account in selecting means and methods of organising youth activities. They can also serve as a basis for the regional youth policy.